2013
DOI: 10.1111/jpim.12041
|View full text |Cite
|
Sign up to set email alerts
|

Clinging to Slim Chances: The Dynamics of Anticipating Regret When Developing New Products

Abstract: This paper focuses on the effects of anticipated regret during large‐scale investment projects—namely new product development. Anticipated regret means worrying about the future, and decision‐makers experience it prior to both making a decision and knowing the outcome of that decision. It is forward‐looking while actual regret is backward‐looking. Decision‐makers must make project continuation/termination decisions with conflicting pressures. If they continue it, they might receive disconfirming information in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 68 publications
(90 reference statements)
0
7
0
Order By: Relevance
“…Despite the obvious importance of this aspect, research on the human cost of innovation project terminations is still in a nascent stage (Moenkemeyer et al, 2012). Most research dealing with innovation project terminations focuses on when and how such a termination should occur (Patzelt, Lechner, and Klaukien, 2011;Sarangee, Schmidt, and Wallman, 2013), for example, by examining factors underlying escalation of commitment (Behrens and Ernst, 2014;Sarangee, Woolley, Schmidt, and Long, 2014;Schmidt and Calantone, 2002). Only a few researchers, in particular Shepherd, Patzelt, and colleagues, have explicitly addressed the negative side effects of terminating innovation projects on the involved individuals that might counteract the intended positive effects behind the termination decisions (Corbett et al, 2007;Shepherd et al, 2011Shepherd et al, , 2013Shepherd et al, , 2014V€ alikangas et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the obvious importance of this aspect, research on the human cost of innovation project terminations is still in a nascent stage (Moenkemeyer et al, 2012). Most research dealing with innovation project terminations focuses on when and how such a termination should occur (Patzelt, Lechner, and Klaukien, 2011;Sarangee, Schmidt, and Wallman, 2013), for example, by examining factors underlying escalation of commitment (Behrens and Ernst, 2014;Sarangee, Woolley, Schmidt, and Long, 2014;Schmidt and Calantone, 2002). Only a few researchers, in particular Shepherd, Patzelt, and colleagues, have explicitly addressed the negative side effects of terminating innovation projects on the involved individuals that might counteract the intended positive effects behind the termination decisions (Corbett et al, 2007;Shepherd et al, 2011Shepherd et al, , 2013Shepherd et al, , 2014V€ alikangas et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Project termination is one of the most difficult decisions in a company (Balachandra & Raelin, 1984;Balachandra, 1984Balachandra, , 1996Cooper & Edgett, 2012;Cooper, 2009a;Sarangee, non-routine characteristics. Routine decisions can rely on a great amount of data in a wellknown environment, making the forecasting more precise.…”
Section: Project Termination As a Project Portfolio Management Decisionmentioning
confidence: 99%
“…Emotions also play a vital role on this subject. Early termination is surrounded by a very peculiar phenomenon called the "anticipation of regret" (Sarangee et al, 2013). Actual regret is backward looking, while the anticipated regret is forward-looking.…”
Section: Project Termination As a Project Portfolio Management Decisionmentioning
confidence: 99%
“…Anticipated regret is a negative emotion generated when individuals believe that they could have achieved a better outcome had they made a different choice. The effect of anticipated regret on decision‐making has been studied in various fields, such as experimental psychology (Zeelenberg, 1999), auction (Engelbrecht‐Wiggans & Katok, 2008), new product development (Sarangee et al, 2013), and operations (Bell, 1982; Perakis & Roels, 2008; Yang et al, 2019). The extant literature (e.g., Lemon et al, 2002; Loomes & Sugden, 1982; Simonson, 1992; Zeelenberg & Pieters, 2007) has also found that anticipated regret affects consumers' purchase decisions, that is, consumers may ex ante make their choices to minimize or alleviate the potential post purchase regret anticipated before purchasing.…”
Section: Literature Reviewmentioning
confidence: 99%